Trade and Investment Rules for Inclusive and Sustainable Development: Nepalese Legal Perspectives - Ingnam, Kumar (Kathmandu School of Law Review, 2013)
Sustainability of development and making investment sustainable are reinforcing and correlated. The investor does not invest unless their investment is permitted and protected by the laws and policies of the host state. There exist a number of principles for investment policymaking for sustainable development within which relationship between investors, host states and local communities is a key requirement. Environmental sustainability, social equity and inclusiveness and economic growth are reinforcing and complementing each other which are the three pillars of sustainable development. Nepal had, at the time of WTO accession, confirmed to amend trade related investments measures regime i.e. Foreign Investment and One Window Policy 1992, Industrial Policy 1992 and others, to ensure the compliance with the WTO Agreement on Trade Related Investment Measure (TRIMS). By now, the laws of Nepal, except few, are in compliance with the WTO standards. Nepal has some prospective areas of investment, mostly based on agriculture and service business. Trade and investment with sustainable development, is a pragmatic approach which encourages upgrading policies and laws. However, investment policy alone cannot provide a ‘one-size-fits-all’ solution for all economies that depends on the eco-socio-political conditions of individual countries.